ELECTROMAGNETIC SHIELDING EFFECTIVENESS OF HYBRID KNITTED FABRICS WITH STAINLESS STEEL WIRE - АРАБУЛІ, А.; БАЙЗІК, В.; КИЗИМЧУК, О. (Technologies and Engineering, 2023)
Purpose. The purpose of this paper was to research innovative and simple approaches toward developing an effective hybrid knitted fabric for electromagnetic shielding application. Methodology. The work uses the basics of textile material science and the theory of knitting, methods of analysis and synthesis of the obtained results. The electromagnetic shielding effectiveness of the hybrid knitted fabrics was measured using a far-field electromagnetic plane wave by the method in ASTM D 4935-18 for planar materials. The shielding efficiency of knitting textiles in the frequency range from 0 GHz to 3 GHz are presented in a paper in terms of the main mechanisms of EMR attenuation: absorption and reflection. Results. A comprehensive evaluation of electromagnetic shielding characteristics of hybrid knitting fabrics has been done in this work. The conductive hybrid fabrics were produced by using cotton yarns and stainless steel wire in 4 types of knitting interlooping (Rib 1+1, Half Milano rib, Half-cardigan and Cardigan) to determine the electromagnetic shielding effectiveness, absorption and reflection values over an incident frequency of 0–3 GHz. For all hybrid knitting samples, a general trend was that shielding effectiveness has peak values of 23÷50 dB in the interval from 200 to 900 MHz. This indicates the "excellent" level of shielding from EMR of the developed hybrid knitted fabric in the indicated frequency range. Scientific novelty. The main factor that determines the shielding ability of knitting textiles is the positioning of the metal components in the structure. The knitted structure of half Milano rib demonstrates the highest shielding efficiency due to the arrangement of the structural elements namely loops and tucks. Practical significance. Hybrid knitted fabrics containing stainless steel wire (the stainless steel wire was fed into the knitting area along with the cotton yarn) have low reflection percentages and high absorption percentages in the entire range of frequencies and may be used as electromagnetic wave absorbents.